1997
DOI: 10.1172/jci119383
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and sequencing of the pancreatic islet neogenesis associated protein (INGAP) gene and its expression in islet neogenesis in hamsters.

Abstract: Induction of islet neogenesis by cellophane wrapping (CW) reverses streptozotocin-induced (STZ) diabetes. Administration of Ilotropin, a protein extract isolated from CW pancreata, causes recapitulation of normal islet ontogeny and reverses STZ diabetes, reducing mortality by 50%. We investigated the hypothesis that a novel gene encoding a constituent of Ilotropin was expressed in the hamster pancreas undergoing islet neogenesis. Islet neogenesis associated protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(161 citation statements)
references
References 35 publications
4
155
0
2
Order By: Relevance
“…The immunocytochemical presence of INGAP has been shown not only in hamsters, but also in the pancreas of normal foetal mice (Rafaeloff-Phail et al 1998a), adult rats (H Del Zotto & C Semakula, unpublished observations), and in human beings (Rafaeloff-Phail et al 1998b, Semakula et al 2002. It has further been reported that INGAP administration to streptozotocin-treated hamsters decreased significantly the percentage of diabetic animals (Rafaeloff et al 1997, Gold et al 1998.…”
Section: Introductionmentioning
confidence: 94%
“…The immunocytochemical presence of INGAP has been shown not only in hamsters, but also in the pancreas of normal foetal mice (Rafaeloff-Phail et al 1998a), adult rats (H Del Zotto & C Semakula, unpublished observations), and in human beings (Rafaeloff-Phail et al 1998b, Semakula et al 2002. It has further been reported that INGAP administration to streptozotocin-treated hamsters decreased significantly the percentage of diabetic animals (Rafaeloff et al 1997, Gold et al 1998.…”
Section: Introductionmentioning
confidence: 94%
“…Gene expression profiling has identified the Reg3 gene family as potentially involved in the stimulatory effect of RKIP1 ablation on pancreatic growth at P28. Interestingly, the Reg3 genes have been previously associated to pancreatic regeneration and islet cell neogenesis [37][38][39][40][41]. Further supporting a role for Reg3 genes in pancreatic postnatal development, a recent study has described the upregulation of Reg3 genes in the mouse pancreas between P7 and P30 followed by their subsequent downregulation in adulthood [42].…”
Section: Discussionmentioning
confidence: 89%
“…[194][195][196] The expression and secretion of another molecule that belongs to the Reg family of proteins, termed islet neogenesis-associated protein (INGAP), is upregulated in hamster islets where neogenesis was artificially induced. 197,198 The precise role of INGAP on b-cell proliferation and function, however, remains unclear.…”
Section: Stem/progenitor Cellsmentioning
confidence: 99%